Evaluation of design criteria for steel fabric reinforced concrete wall panel in high rise building / Khamsiah Hj. Md. Shahid - Md. Shahid, Khamsiah (Faculty of Civil Engineering, 2008)
Design criteria of a structure are a vital element when design process takes place. An understanding about the structure will give vast effect to safety aspect of the structure design. Safety aspects come extra fragile when it involves high rise structure. A design guideline therefore needed in order to serve this condition. There are a lot of guideline and standard of concrete design giving guideline about the concrete structure but some did not provide guidelines for high rise building. In Malaysia designer always refer to BS 8110 as their guideline, but whether the guideline is the best there is not proven. In the evaluation of design criteria for steel fabric reinforced concrete wall panel in high rise building, three standard code of design for concrete structure are used as a comparison. The three design code are British standard (BS 8110), American standard (ACI 318), and Australian standard (AS 3600). These standards code of design are compared under six major design criteria such as structural stability, design axial load, effective height, design moment slenderness ratio and deflection. The comparison done covers what the codes have and had leave out. Besides that, the similarity and differences among the three design code, BS 8110, AS 3600 and ACI 318 also had been point out. Throughout the study it was found that BS 8110, treated a design under all the design criteria that had been studied. AS 3600 only cover a part of the studied design criteria. As well as AS 3600, ACI 318 also not covers all aspect of the design criteria that had studied. However, conclusion cannot be made to state that the two design code were deficient because the leave out design criteria might had been treated in other means and yet this two design code were well followed in their country safely.